Capacitor recruitment fusion methodology: a case study - Cabrita, Susana (2020)
The Project entitled Methodology for Recruitment Capacitor: a case study (Fusion Resourcing - A case study) emerged from a need of the firm Innovagency SA that operates in the technological field and in the digital communication field. This need is associated with the difficulty of recruiting programmers with specific technical knowledge and skills related to the most sophisticated technology platforms, currently used on the web. It presents the design and implementation of a synergetic fusion, recruitment, selection, and training and integration solution supported by a "Trainee Academy" called "i9.station". Based on the results obtained, the interest and potential of this fusion approach it is approve. Both in terms of recruitment effectiveness and the effectiveness of the selection process associated with training, as well as in the speed and strength of both competency acquisition and process of socio-professional and technical integration in the firm and in the work teams, proving, above all, an investment capable of generating generous positive returns.